Efektivitas Manajemen Pendidikan untuk Membangun Ketahanan Komunitas Ditinjau dari Zakat dan Resiliensi Ekonomi - Fitri Uswatun Khasanah; Welius Purbonuswanto; Saryanto Saryanto; Yudhi Purwa Nugraha (Universitas Negeri Malang, 2026)
Abstract: Traditionally, disaster management has tended to focus predominantly on the response and recovery phases following the occurrence of a disaster. The transition toward a proactive disaster preparedness approach requires significant investment in what is referred to as disaster preparedness education management. This study aims to examine the effectiveness of disaster preparedness education management in strengthening community resilience, taking into account the roles of zakat and economic resilience. This study adopts a quantitative approach with a factorial design, complemented by mediation analysis to test causal relationships among variables and to investigate the mediating role in explaining the mechanism through which the independent variables affect the dependent variable. A total of 106 islamic boarding school students (siswa) participated in this study. The results of the Tests of Between-Subjects Effects (ANOVA) revealed a statistically significant main effect of the intervention on the enhancement of community resilience. Moreover, the mediation analysis demonstrates that economic resilience serves as a principal mediating variable that explains the mechanism through which disaster preparedness is transformed into community resilience. Zakat funds should be optimized by shifting assistance strategies from short-term consumptive support toward long-term human capital investment. These funds may be distributed through sustainable educational scholarship schemes and the provision of entrepreneurial capital for economically vulnerable siswa families. Keywords: Community Resilience; Economic Resilience Abstrak: Secara tradisional, manajemen bencana cenderung dominan pada fase respons dan pemulihan setelah bencana terjadi. Transisi menuju pendekatan kesiapsiagan bencana yang proaktif menuntut investasi yang signifikan dalam apa yang disebut sebagai manajemen pendidikan kesiapsiagan bencana. Tujuan umum penelitian adalah menganalisis efektivitas manajemen pendidikan kesiapsiagaan bencana dalam membangun ketahanan komunitas, dengan mempertimbangkan peran zakat dan resiliensi ekonomi. Penelitian ini menggunakan pendekatan kuantitatif dengan desain faktorial yang dilanjutkan dengan desain mediasi untuk menguji hubungan kausal antarvariabel serta peran variabel mediator dalam menjelaskan mekanisme pengaruh variabel independen terhadap variabel dependen. Subjek penelitian sebanyak 106 siswa. Berdasarkan hasil analisis menggunakan Tests of Between-Subjects Effects (ANOVA), ditemukan efek utama yang signifikan dari intervensi terhadap peningkatan ketahanan komunitas. Selanjutnya hasil analisis mediasi menunjukan bahwa resiliensi ekonomi berperan sebagai penghubung utama yang menentukan keberhasilan transformasi kesiapsiagaan bencana menjadi ketahanan komunitas. Dana zakat perlu dioptimalkan melalui pergeseran strategi bantuan dari yang bersifat konsumtif menjadi investasi modal manusia. Dana zakat dapat disalurkan melalui program beasiswa pendidikan berkelanjutan dan pemberian modal usaha bagi keluarga siswa yang rentan secara ekonomi. Kata kunci: Disaster Preparedness Education Management, Ketahanan Komunitas, Resiliensi Ekonomi